A biodegradable composite lubricant
By using modified wear-resistant materials and multi-layer graphene in composite lubricating oils to form a large pore structure, the problem of insufficient durability and wear resistance of existing lubricating oils is solved, and higher durability and lubricating effects are achieved. At the same time, biodegradability is maintained.
Patent Information
- Application Number
- CN202411074521.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-08-07
AI Technical Summary
The existing biodegradable composite lubricating oil has low durability, service life and wear resistance.
By using modified wear-resistant materials in lubricating oils, including silicon nitride and titanium diboride microspheres coated with silica, and by combining multilayer graphene and pore-generating agent, a large pore structure is formed to enhance the Dispersibility and storage capacity.
It significantly improves the durability, wear resistance and service life of lubricating oil, enhances the lubricating effect, reduces the coefficient of friction and wear, and maintains the biodegradable characteristics.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lubricating oils, and in particular to a biodegradable composite lubricating oil. Background Art
[0002] Lubricating oil is widely used in aviation, automobile, mechanical processing, transportation, metallurgy, coal, construction, light industry and other industries. Most of the traditional lubricating oils are based on mineral oil, which plays a huge role in reducing friction and wear, saving energy, extending the life of machinery and meeting the lubrication needs under harsh working conditions. However, when it is used in large quantities, it will inevitably enter the environment through various channels such as transportation, leakage, splashing, overflow or improper discharge, seriously polluting soil and water resources, and destroying the ecological environment and ecological balance.
[0003] For example, the Chinese patent, application number CN202210377117.6, is a biodegradable composite lubricant, the raw materials of each component of the composite lubricant include: by weight, 4-6 parts of modified wear-resistant material, 3-4 parts of additives, 10-15 parts of phosphoric acid, 15-18 parts of n-octadecyl alcohol, 30-40 parts of vegetable oil, 2-3 parts of oleic acid surfactant, 2-3 parts of antioxidant, 2-3 parts of extreme pressure agent, 1-2 parts of defoaming agent, 5-6 parts of viscosity modifier, 15-20 parts of water; the vegetable oil includes castor oil and cottonseed oil, and the mass ratio of castor oil to cottonseed oil is 1:1; the modified wear-resistant material is oil-soluble microspheres, and the microspheres are mainly made of silica-coated fillers. The invention discloses a biodegradable composite lubricant and its preparation process, the process design is reasonable, the operation is simple, the prepared lubricant has excellent anti-wear and friction reduction properties, good lubrication performance, good storage stability, biodegradability, no damage to the ecological environment, practical and environmentally friendly.
[0004] However, its durability, service life and wear resistance still need to be improved. Summary of the invention
[0005] The embodiments of the present application provide a biodegradable composite lubricant, thereby solving the problems of low wear resistance and service life in the prior art, and achieving durability and high wear resistance of the lubricant.
[0006] The embodiment of the present application provides a biodegradable composite lubricant, wherein the raw materials of each component include by weight: 5 parts of modified wear-resistant material, 2 parts of multilayer graphene, 3.5 parts of additives, 12 parts of phosphoric acid, 17 parts of n-octadecyl alcohol, 35 parts of vegetable oil, 2.5 parts of oleic acid surfactant, 2 parts of antioxidant, 2.5 parts of extreme pressure agent, 1.5 parts of defoaming agent, 5 parts of viscosity modifier, and 18 parts of water;
[0007] The modified wear-resistant material is an oil-soluble microsphere, which is made of a silica-coated filler and has two layers. The inner layer filler includes silicon nitride and titanium diboride, and the mass ratio of silicon nitride to titanium diboride is 1:2; the outer layer is ethyl orthosilicate, and the porogens used in the inner and outer layers are different.
[0008] Furthermore, the vegetable oil includes castor oil and cottonseed oil, and the mass ratio of castor oil to cottonseed oil is 1:1.
[0009] Furthermore, the additive is mainly prepared by reacting benzotriazole and formaldehyde.
[0010] Furthermore, the preparation process of the composite lubricating oil comprises the following specific steps:
[0011] (1) Silicon nitride and titanium diboride were mixed and stirred for 15 minutes, isopropanol was added, ultrasonic dispersion was performed for 25 minutes, a mixed solution of ammonia water, deionized water and isopropanol was added, and stirring was performed for 8 minutes. TEOS and isopropanol were added, and stirring was performed for 12 minutes. A porogen was added, and the mixture was reacted at a constant temperature of 43°C in a water bath for 1.5 hours, and the mixture was heated to 88°C and refluxed for 2.5 hours. After the reaction, the mixture was centrifuged and washed, and vacuum dried to obtain material A; the porogen was octadecylamine; material A was heated to 350°C, calcined for 4 hours, and cooled to room temperature to obtain a wear-resistant material; the heating rate during calcination was 1.5°C / min;
[0012] (2) Take the wear-resistant material, place it in cyclohexane, ultrasonically disperse it for 1 hour, add oleic acid and concentrated sulfuric acid, stir and react at 73°C for 5 hours, filter and separate, wash with anhydrous ethanol, and vacuum dry at 75°C to obtain a modified wear-resistant material;
[0013] (3) Take benzotriazole, water and formaldehyde, mix and stir evenly, keep warm at 78°C for 32 minutes, cool, filter, and obtain an additive;
[0014] (4) Take the modified wear-resistant material, multilayer graphene and additives, add phosphoric acid and n-octadecyl alcohol, heat to 110°C for reaction, add vegetable oil and oleic acid surfactant after the reaction, ultrasonically disperse for 5 minutes, then add antioxidant, extreme pressure agent, defoaming agent, viscosity regulator and water, stir evenly, let stand for 22 hours, and obtain the finished product.
[0015] Furthermore, in step (2), the reaction was stirred at 73°C for 5 hours and then cooled to 50°C and stirred for 5 hours.
[0016] Furthermore, in step (2), the modified wear-resistant material is also subjected to secondary coating, specifically: the obtained modified wear-resistant material is ultrasonically dispersed in cyclohexane, and tetraethyl orthosilicate and dodecylamine are added as the second porogen; oleic acid and concentrated sulfuric acid are added, and the mixture is stirred and reacted at 73°C for 5 hours, and then the temperature is lowered to 50°C and stirred for 5 hours, filtered and separated, washed with anhydrous ethanol, and vacuum dried at 75°C to obtain a double-layer modified wear-resistant material.
[0017] Furthermore, the weight of the ethyl orthosilicate and the silica coated filler are equal.
[0018] Furthermore, the wear-resistant material is pretreated before modification.
[0019] Furthermore, the wear-resistant material is pretreated by heating the wear-resistant material to 600-800° C. for 1-2 hours and then immediately placing it in cyclohexane.
[0020] Further, the temperature of cyclohexane is -20°C.
[0021] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages:
[0022] First, octadecylamine as a porogen increases the size of the pores. The large pore structure makes the wear-resistant microspheres and multilayer graphene more dispersed in the lubricating oil, and is not easy to agglomerate, so as to maintain the uniformity of the lubricating oil and improve its lubricating effect. The large pore structure also stores more lubricating oil, so that it can continuously provide lubrication during the friction process, reduce the friction coefficient, and reduce wear. Increasing the pore size is conducive to better storage and release of lubricating oil additives during the use of the lubricating oil, improving the durability and wear resistance of the lubricating oil; and improving the service life and wear resistance of the lubricating oil.
[0023] Secondly, the thickness of the silica layer is increased by increasing the stirring time, and the relative movement speed of the materials is further reduced by the subsequent lowering of the stirring temperature to increase the contact time and increase the thickness of the silica layer; the initial reaction at high temperature causes the chemical bonding between the surface of the wear-resistant material and reactants such as oleic acid and concentrated sulfuric acid to form a preliminary modified layer, and the subsequent cooling reaction further consolidates and thickens this layer, making the silica layer thicker; a thicker silica layer can provide stronger protection, reduce the direct contact between the wear-resistant filler and the lubricating oil, extend the service life of the wear-resistant filler, improve the durability of the wear-resistant filler, and extend the overall life of the lubricating oil;
[0024] Third, the second thinner silica layer can be more easily broken when squeezed, releasing the silica particles inside; the silica particles formed inside can further provide lubrication and friction reduction effects during the friction process; the double-layer structure design combines the advantages of pores of different sizes, which can not only effectively store lubricant additives, but also gradually release them during use to improve the lubrication effect; the silica particles inside play an additional lubricating and friction-reducing role during the friction process, significantly improving the anti-wear performance of the lubricant;
[0025] Fourth, the wear-resistant material is heated to 600-800℃ for 1-2h to remove impurities in the wear-resistant material, improve its crystal structure, and increase its surface activity, thereby improving its wear resistance. It is then immediately placed in cyclohexane at -20℃ for sudden cooling, which enhances the internal structure of the wear-resistant material, improves the strength and toughness of the wear-resistant material, and forms cracks or microcracks on the surface and near-surface area of the wear-resistant material; these tiny structures increase the specific surface area of the wear-resistant material, provide more reaction sites for subsequent modification treatments, increase the contact area between the wear-resistant material and other materials or media, and improve its adhesion and friction properties; the presence of cracks and microcracks makes it easier for oleic acid to penetrate into the wear-resistant material and undergo a grafting reaction with silica particles, thereby improving the dispersibility and stability of the wear-resistant material in oil. DETAILED DESCRIPTION
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.
[0027] Embodiment 1: The present application discloses a biodegradable composite lubricant, wherein the raw materials of each component include by weight: 5 parts of modified wear-resistant material, 2 parts of multilayer graphene, 3.5 parts of additives, 12 parts of phosphoric acid, 17 parts of n-octadecyl alcohol, 35 parts of vegetable oil, 2.5 parts of oleic acid surfactant, 2 parts of antioxidant, 2.5 parts of extreme pressure agent, 1.5 parts of defoaming agent, 5 parts of viscosity modifier, and 18 parts of water;
[0028] The vegetable oil includes castor oil and cottonseed oil, and the mass ratio of castor oil to cottonseed oil is 1:1;
[0029] The modified wear-resistant material is an oil-soluble microsphere, which is mainly made of a filler coated with silicon dioxide. The filler includes silicon nitride and titanium diboride, and the mass ratio of silicon nitride to titanium diboride is 1:2.
[0030] The additive is mainly prepared by reaction of benzotriazole and formaldehyde;
[0031] The preparation process of the composite lubricating oil comprises the following specific steps:
[0032] (1) Silicon nitride and titanium diboride were mixed and stirred for 15 minutes, isopropanol was added, ultrasonic dispersion was performed for 25 minutes, a mixed solution of ammonia water, deionized water and isopropanol was added, and stirring was performed for 8 minutes. TEOS and isopropanol were added, and stirring was performed for 12 minutes. A porogen was added, and the mixture was reacted at a constant temperature of 43°C in a water bath for 1.5 hours, and the mixture was heated to 88°C and refluxed for 2.5 hours. After the reaction, the mixture was centrifuged and washed, and vacuum dried to obtain material A; the porogen was octadecylamine; material A was heated to 350°C, calcined for 4 hours, and cooled to room temperature to obtain a wear-resistant material; the heating rate during calcination was 1.5°C / min;
[0033] (2) Take the wear-resistant material, place it in cyclohexane, ultrasonically disperse it for 1 hour, add oleic acid and concentrated sulfuric acid, stir and react at 73°C for 5 hours, filter and separate, wash with anhydrous ethanol, and vacuum dry at 75°C to obtain a modified wear-resistant material;
[0034] (3) Take benzotriazole, water and formaldehyde, mix and stir evenly, keep warm at 78°C for 32 minutes, cool, filter, and obtain an additive;
[0035] (4) Take the modified wear-resistant material, multilayer graphene and additives, add phosphoric acid and n-octadecyl alcohol, heat to 110°C for reaction, add vegetable oil and oleic acid surfactant after the reaction, ultrasonically disperse for 5 minutes, then add antioxidant, extreme pressure agent, defoaming agent, viscosity regulator and water, stir evenly, let stand for 22 hours, and obtain the finished product.
[0036] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0037] By adding a porogen, a porous structure can be formed in the wear-resistant microspheres, and after the calcination process, a porous structure is formed in the wear-resistant microspheres, so that the lubricating oil has better lubrication performance, wear resistance and dispersibility; the porogen will occupy space in the formation process of the wear-resistant microspheres, and in the subsequent calcination process, the porogen will be burned off, leaving pores in the microspheres; the microspheres have a larger specific surface area, and their adsorption and lubrication capabilities are improved; octadecylamine as a porogen increases the size of the pores, and the large pore structure makes the wear-resistant microspheres and multilayer graphene more dispersible in the lubricating oil, not easy to agglomerate, maintain the uniformity of the lubricating oil, and improve its lubrication effect; the large pore structure also stores more lubricating oil, so that it can continuously provide lubrication during the friction process, reduce the friction coefficient, and reduce wear; increasing the pore size is conducive to better storage and release of lubricating oil additives during the use of the lubricating oil, improve the durability and wear resistance of the lubricating oil, and improve the service life and wear resistance of the lubricating oil;
[0038] Because lubricating oil has excellent lubricating and wear-resistant properties, it can reduce friction and wear of equipment and extend its service life; good lubricating properties can reduce the friction resistance of equipment, thereby improving its operating efficiency; the biodegradability of lubricating oil means that it will not cause long-term pollution to the environment during use, and meets environmental protection requirements.
[0039] Example 2: The above example uses octadecylamine to increase the pore size of silica microspheres, so that the lubricant can better store and release lubricant additives during use, thereby improving the durability and wear resistance of the lubricant. In order to improve the durability of the wear-resistant filler, the thickness of the silica coating layer is increased, which is further improved on the basis of Example 1.
[0040] (2) Take the wear-resistant material, place it in cyclohexane, ultrasonically disperse it for 1 hour, add oleic acid and concentrated sulfuric acid, stir and react at 73°C for 5 hours, then cool to 50°C and stir for 5 hours, filter and separate, wash with anhydrous ethanol, and vacuum dry at 75°C to obtain a modified wear-resistant material.
[0041] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0042] The thickness of the silica layer is increased by increasing the stirring time, and the relative movement speed of the materials is further reduced by the subsequent stirring temperature reduction to increase the contact time and increase the thickness of the silica layer; the initial reaction at high temperature causes the chemical bonding between the surface of the wear-resistant material and the reactants such as oleic acid and concentrated sulfuric acid to form a preliminary modified layer, and the subsequent cooling reaction further consolidates and thickens this layer, making the silica layer thicker;
[0043] Thicker silica layer can provide stronger protection, reduce the direct contact between wear-resistant filler and lubricant, extend the service life of wear-resistant filler, improve the durability of wear-resistant filler and extend the overall life of lubricant;
[0044] It has higher hardness and wear resistance, which can significantly improve the overall wear resistance of wear-resistant materials, change the physical and chemical properties of wear-resistant materials such as surface roughness and wettability, and make them more suitable for specific application scenarios; modification treatment enhances the resistance of wear-resistant materials to acid, alkali and other chemical substances, and prolongs their service life;
[0045] The modified wear-resistant materials may be suitable for more types of working environments and conditions, such as high temperature, high pressure, strong corrosive environment and other harsh environments; through modification, the performance of the wear-resistant materials is improved, thereby improving the quality and reliability of the final product; because the modified wear-resistant materials have a longer service life and better performance stability, the replacement frequency and maintenance costs can be reduced.
[0046] Embodiment 3: Embodiment 2 extends the service life of the wear-resistant filler by extending the reaction time, increasing the thickness of the silicon dioxide layer, reducing the direct contact between the wear-resistant filler and the lubricating oil; in order to improve the lubrication effect, a secondary load is performed, which is further improved on the basis of Embodiment 2.
[0047] (2) Take the wear-resistant material, place it in cyclohexane, ultrasonically disperse it for 1 hour, add oleic acid and concentrated sulfuric acid, stir and react at 73°C for 5 hours, then cool it to 50°C and stir it for 5 hours, filter and separate it, wash it with anhydrous ethanol, and vacuum dry it at 75°C to obtain a modified wear-resistant material; ultrasonically disperse the obtained modified wear-resistant material in cyclohexane, add ethyl orthosilicate and dodecylamine in an amount equal to the weight of the silica-coated filler as a second porogen; add oleic acid and concentrated sulfuric acid, stir and react at 73°C for 5 hours, then cool it to 50°C and stir it for 5 hours, filter and separate it, wash it with anhydrous ethanol, and vacuum dry it at 75°C to obtain a double-layer modified wear-resistant material.
[0048] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0049] The second thinner silica layer can be more easily broken when squeezed, releasing the silica particles inside; the silica particles formed inside can further provide lubrication and friction reduction effects during the friction process; the double-layer structure design combines the advantages of pores of different sizes, which can not only effectively store lubricant additives, but also gradually release them during use to improve the lubrication effect; the silica particles inside play an additional lubricating and friction-reducing role during the friction process, significantly improving the anti-wear performance of the lubricant;
[0050] Through the evolution of the above technical solutions, not only the wear resistance and service life of the lubricant are improved, but also the lubricating effect and durability of the lubricant are further enhanced through the design of double-layer silica loading; the silica particles formed inside provide additional friction reduction during the friction process, so that the lubricant can maintain excellent performance in a variety of working environments; in addition, the biodegradable characteristics make the lubricant also have significant advantages in environmental protection;
[0051] The small pore structure increases the hardness and density of the wear-resistant material surface, improves its wear resistance, reduces the wear area of the material surface, and prolongs its service life; it also makes the wear-resistant material surface smoother, reduces the friction coefficient, improves the operating efficiency of the product, and enhances the chemical stability of the wear-resistant material. The small pore structure further reduces the contact area between the chemical substance and the internal structure of the wear-resistant material, thereby improving its corrosion resistance;
[0052] The large void structure makes the wear-resistant material have good air permeability, improves heat dissipation or gas exchange, and provides more adsorption sites, so that the wear-resistant material can adsorb more liquid or gas molecules, which is suitable for filtration, separation and other fields. Compared with the dense structure, the large void structure reduces the weight of the wear-resistant material while maintaining a certain strength, thereby reducing the weight and cost of the overall product;
[0053] The small pore structure of the outer layer provides excellent wear resistance and surface finish, while the large pore structure of the inner layer enhances air permeability and adsorption performance, making the modified wear-resistant material perform well in many aspects and suitable for more complex and demanding application environments; the different pore structures of the outer and inner layers achieve a gradient change in performance, and the thickness and pore size of each layer are adjusted according to specific needs to achieve the best performance balance, which provides the possibility for customized production of wear-resistant materials; the small pore structure of the outer layer protects the large pore structure of the inner layer from direct wear and corrosion, thereby extending the overall service life. At the same time, the large pore structure of the inner layer is conducive to heat dissipation and gas exchange, reducing the risk of damage caused by overheating or excessive internal pressure.
[0054] Embodiment 4: Embodiment 3 improves the durability of the wear-resistant filler and extends the overall life of the lubricating oil through the double-layer modified wear-resistant material. In order to improve the wear resistance and lubrication effect, heating and extreme cold treatment are performed to further improve the embodiment 3.
[0055] (2) Take the wear-resistant material and heat it to 600-800℃ for 1-2h, then immediately place it in cyclohexane at -20℃, wait until the temperature no longer changes, then ultrasonically disperse it for 1h, add oleic acid and concentrated sulfuric acid, stir and react at 73℃ for 5h, then cool it to 50℃ and stir it for 5h, filter and separate it, wash it with anhydrous ethanol, and vacuum dry it at 75℃ to obtain a modified wear-resistant material; ultrasonically disperse the obtained modified wear-resistant material in cyclohexane, add ethyl orthosilicate and dodecylamine in an amount equal to the weight of the silica-coated filler as a second porogen; add oleic acid and concentrated sulfuric acid, stir and react at 73℃ for 5h, then cool it to 50℃ and stir it for 5h, filter and separate it, wash it with anhydrous ethanol, and vacuum dry it at 75℃ to obtain a double-layer modified wear-resistant material.
[0056] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0057] The wear-resistant material is heated to 600-800℃ for 1-2h to remove impurities in the wear-resistant material, improve its crystal structure, and increase its surface activity, thereby improving its wear resistance. It is then immediately placed in cyclohexane at -20℃ for rapid cooling, which strengthens the internal structure of the wear-resistant material, improves the strength and toughness of the wear-resistant material, and forms cracks or microcracks on the surface and near-surface area of the wear-resistant material; these microstructures increase the specific surface area of the wear-resistant material, providing more reaction sites for subsequent modification treatments; increasing the contact area between the wear-resistant material and other materials or media, and improving its adhesion and friction performance;
[0058] The presence of cracks and microcracks makes it easier for oleic acid to penetrate into the wear-resistant material and undergo grafting reaction with silica particles, thereby improving the dispersibility and stability of the wear-resistant material in the oil;
[0059] The modified wear-resistant material is easier to break under friction and pressure. The broken silica particles interact with the base oil to form a mixed oil film, which synergistically enhances the lubrication effect. At the same time, the presence of cracks and microcracks also helps to store lubricating oil and improve the sustainability and stability of the lubricating film.
[0060] As stress concentration areas, cracks and microcracks can absorb and release part of the stress during subsequent use, thereby slowing down the accumulation of overall stress of the wear-resistant material and improving its fatigue resistance and service life; the modified wear-resistant material has better wear resistance and can maintain a longer service life under extreme conditions; by promoting the grafting of oleic acid and the formation of mixed oil film, the lubricating performance of the lubricating oil is improved and the wear of mechanical parts is reduced; the presence of cracks and microcracks enables the lubricating oil to be evenly distributed and stored on the surface of the wear-resistant material, improving the overall stability of the lubrication system; cracks and microcracks improve the balance between the strength and toughness of the wear-resistant material, making it both hard to resist wear and tough to resist impact and fracture; the presence of cracks and microcracks also has a positive effect on the thermal stability of the wear-resistant material, reducing the risk of thermal stress concentration and failure at high temperatures by adjusting the thermal stress distribution and heat dissipation path;
[0061] This technical solution is based on biodegradable raw materials and processes, which conforms to the development trend of green environmental protection and is conducive to reducing pollution to the environment; the heating and extreme cold treatment steps are relatively simple and highly controllable, and can be adjusted and optimized on the existing production line, reducing production costs and cycles; through the implementation of the above technical solution, the wear resistance and lubrication performance of the lubricant are significantly improved, while maintaining its environmentally friendly and sustainable characteristics, providing higher performance and lower cost solutions for related industries.
[0062] The finished products prepared from Examples 1 to 4 and the comparative example (a biodegradable composite lubricant with application number CN202210377117.6) were tested for friction performance. The testing instrument was an MRS-10B four-ball friction and wear tester. The standards GB / T3142-1982, SH / T0189, and SH / T0762 were implemented. The biodegradation rate was recorded according to GB / T19277. The friction performance was tested for 15 days at 60°C and 50% humidity. The results are as follows:
[0063]
[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A biodegradable composite lubricant, characterized in that: The raw materials of each component include, by weight: 5 parts of modified wear-resistant material, 2 parts of multilayer graphene, 3.5 parts of additives, 12 parts of phosphoric acid, 17 parts of n-octadecyl alcohol, 35 parts of vegetable oil, 2.5 parts of oleic acid surfactant, 2 parts of antioxidant, 2.5 parts of extreme pressure agent, 1.5 parts of defoaming agent, 5 parts of viscosity modifier, and 18 parts of water; The modified wear-resistant material is an oil-soluble microsphere, which is made of silica-coated fillers. The fillers include silicon nitride and titanium diboride, and the mass ratio of silicon nitride to titanium diboride is 1:2; the outer silica layer has two layers with different pore sizes, and the two layers use different porogens, which are octadecylamine and dodecylamine. Among them, the porogen used in the layer with a larger pore size in the outer silica layer is octadecylamine, and the porogen used in the layer with a smaller pore size is dodecylamine.
Citation Information
Patent Citations
A biodegradable composite lubricant
CN114836255B
Biodegradable composite lubricating oil and preparation process thereof
CN113046153A